Best manufacturing practices and firm performance in the context of Vietnam’s mechanical enterprises - Dao, Minh Anh (Journal of International Economics and Management, 2019)
The results of past studies show that applying best manufacturing practices has promoted firms to improve performance with mixed success. This study aims to examine the extent to which mechanical firms in Vietnam context have adopted best manufacturing practices and whether these practices contribute to firm performance. A structured questionnaire has been developed based on literature of best practices known as world-class. Out of the 204 questionnaires sent, 122 completed replies were received and valid. The data were analyzed using descriptive statistics and regression analysis. The results show that most of best manufacturing practices are adopted and implemented with fairly high degree of acceptance. Three over fourteen best practices (JIT delivery by suppliers, supplier quality management and equipment layout) are proved to be significant and positively related to financial performance, while four over fourteen best practices (JIT delivery by suppliers, cleanliness and organization, Kanban and maintenance) are significantly and positively related to nonfinancial performance. Implications, recommendations and future research are discussed.